Undang-Undang Keterbukaan Informasi Publik dan Penyelenggaraan Pemerintahan - SUSANTO, EKO HARRY (Universitas Muhammadiyah Yogyakarta, 2013)
The freedom of communication which has spread in the society become stronger in support from Transparation of Information Act. But it also doesn’t mean that, the government alignments to the people in such short term can be much better than it was used to. Because, the regulation itself has been trying to create the people of information aside all of the excep¬tions of public information. But if the rule’s not supported by any technical terms that satisfying, it is feared that it can’t be fully used as a tool that can wipe out corruption or even give the society a better service than before. Key words: transparation of information, corruption, public service